Electrode modifications with electrophoretic deposition methods for water electrolyzers - KOCA, ATIF (My University, 2024)
This review covers the methods of hydrogen production through water electrolysis, encountered problems, used catalysts, methods of preparing these catalysts, and especially the method of electrode modification using the electrophoretic deposition technique. The methods of hydrogen production mechanism, electrode and electrocatalyst structures, and electrode modification techniques are classified based on types of the electrolyzers namely Alkaline Water Electrolysis (AEL), Anion Exchange Membrane (AEM) Water Electrolysis, Proton Exchange Membrane Electrolysis (PEMEL) and Solid Oxide Electrolysis (SOEL). The mechanisms of hydrogen evolution and oxygen evolution reactions, which are crucial in hydrogen production, have been provided in all types of electrolyzers. The parameters influencing these reactions on the anode and cathode electrodes have been discussed. This review summarizes and compares important parameters that show the catalyst\"s performance in detail. The fundamental principles of the electrophoretic deposition technique have been explained, and examples of electrocatalysts prepared using this technique have been provided.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; ENERJİ VE YAKITLAR; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; ENERGY & FUELS; PHYSICS, CONDENSED MATTER; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Yakıt Teknolojisi; Yoğun Madde Fiziği; Enerji Mühendisliği ve Güç Teknolojisi; Renewable Energy, Sustainability and the Environment; Physical Sciences; Fuel Technology; Condensed Matter Physics; Energy Engineering and Power Technology; Electrocatalysts; Electrode modification; Electrophoretic deposition; Hydrogen evolution reaction; Oxygen evolution reaction; Water electrolyzers